2020
DOI: 10.2147/ijgm.s284133
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Prevalence of Isolated Neutropenia at High Altitude in Southern Saudi Arabia: Does Altitude Affect Leucocyte Count?</p>

Abstract: Introduction: Isolated neutropenia is a common problem in hematology practice. Benign ethnic neutropenia (BEN) is the common form of neutropenia worldwide and it affects mainly African and Middle Eastern ethnicities. Most cases of isolated mild and moderate neutropenia are benign and associated with no clinical significance. The aim of this study was to estimate the prevalence of isolated neutropenia at high-altitude southern Saudi Arabia. Methods: A large dataset of complete blood counts (CBCs) was analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
8
2
Order By: Relevance
“…The current study validates our previous findings in which the prevalence of neutropenia was found to be 18%. 14 The findings of this study are consistent with those of Gari et al 12 who also reported a high prevalence (20%) of neutropenia in Jeddah. Several other studies have shown a variable frequency of neutropenia among different populations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study validates our previous findings in which the prevalence of neutropenia was found to be 18%. 14 The findings of this study are consistent with those of Gari et al 12 who also reported a high prevalence (20%) of neutropenia in Jeddah. Several other studies have shown a variable frequency of neutropenia among different populations.…”
Section: Discussionsupporting
confidence: 92%
“…We previously noticed a higher prevalence of isolated neutropenia at a high altitude in comparison with sea level. 14 In this study, the prevalence of isolated neutropenia in Taif city (1898 m above sea level) was not different from that in the coastal Jeddah city in the current study. Furthermore, in this study, we did not find any association between altitude levels and hematocrit (as a surrogate for decreased plasma volumes).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We previously noticed a higher prevalence of isolated neutropenia at a high altitude in comparison with sea level [12]. In this study, the prevalence of isolated neutropenia in Taif city (1,898 m above sea level) was not different from that in the coastal Jeddah city in the current study.…”
Section: Discussioncontrasting
confidence: 60%
“…BEN is most common in Africans, Afro-Americans, Ethiopian Jews, and Yemenite Jews [6,[9][10][11]. We previously showed that a higher prevalence of isolated neutropenia was observed in two cities (Jeddah and Abha) in Saudi Arabia [12]. We aimed to confirm our previous findings through a large sample size from seven different cities (Jeddah, Taif, Al Baha, Abha, Khamis Mushait, Najran, and Gizan) in Southern and Southwestern Saudi Arabia.…”
Section: Introductionmentioning
confidence: 58%